2012
DOI: 10.1155/2012/434171
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Herbal Drug Use on Adverse Drug Reaction Profiles of Patients on Antiretroviral Therapy in Zimbabwe

Abstract: Background. The main objective was to determine the impact of herbal drug use on adverse drug reactions in patients on antiretroviral therapy (ART). Methodology. Patients receiving first-line ART from the national roll-out program participated in this cross-sectional study. Participants were interviewed and a data collection sheet was used to collect information from the corresponding medical record. Results. The majority (98.2%) of participants were using at least one herbal drug together with ART. The most c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
1
17
1
Order By: Relevance
“…Bepe et al (2011) observed that abdominal pain (odds ratio = 3.0, p-value < 0.01) and rash (odds ratio = 2.5, p-value < 0.02) are the adverse events significantly associated with herbal drug use during antiretroviral therapy. The findings of this study are unlike what was observed by Mudzviti et al (2012) who reported that Patients who used the indigenous herbs Musakavakadzi and Peltoforum africanum were less likely to develop adverse drug reactions compared to patients who did not use the herbs.…”
Section: The Association Between Herbal Medicine Use and Occurrence Ocontrasting
confidence: 99%
See 1 more Smart Citation
“…Bepe et al (2011) observed that abdominal pain (odds ratio = 3.0, p-value < 0.01) and rash (odds ratio = 2.5, p-value < 0.02) are the adverse events significantly associated with herbal drug use during antiretroviral therapy. The findings of this study are unlike what was observed by Mudzviti et al (2012) who reported that Patients who used the indigenous herbs Musakavakadzi and Peltoforum africanum were less likely to develop adverse drug reactions compared to patients who did not use the herbs.…”
Section: The Association Between Herbal Medicine Use and Occurrence Ocontrasting
confidence: 99%
“…A study by Masenyetse et al (2015) established that 37% of the patients on Highly active antiretroviral drugs experienced adverse drug reactions. The findings of this study correspond with those of Mudzviti et al (2012) who observed that 70.4% of the patients experienced at least one ADR during ART treatment.…”
Section: Side Effects Experienced By Hiv Positive Patients On Haartsupporting
confidence: 91%
“…It is known that the relative risk of anti-tuberculous therapy-induced hepatotoxicity is higher in HBV/HIV co-infected patients than in HIV mono-infected individuals [ 28 ]. Symptomatic liver disease (particularly, jaundice) frequently prompts patients to seek alternative drugs, a common feature in African HIV populations [ 29 , 30 ], and/or which lead to treatment interruption and change to less potent regimens. If this had contributed in deaths in the present study cohort, such patients might have died at home, or away from the hospital affiliated to APIN and therefore may have be under represented in our data set.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and animal experimental studies have ascertained the negative influence of HAART on sperm functional parameters, sexual hormones, testicular structure, germinal cell development, as well as testicular carbohydrate and lipid metabolism (9,11). With the high financial burden of sustaining compliance with antiretroviral regimens, there is a major challenge of people living with HIV/AIDS (PLWHAs) (12) most especially among sub-Saharan Africa necessitating majority of them resorting to the use of traditional medicines and products (13,14) for improvement of their well-being. Besides, scientific interest towards the use of medicinal plants has been on the rise due to their perceived effectiveness during treatment, relatively low costs and minimal side-effects (15).…”
Section: Introductionmentioning
confidence: 99%